Travel medicine in primary health care - Korzeniewski, Krzysztof (Family Medicine & Primary Care Review, 2017)
Over the last several decades, there has been a rapid growth in international travel all around the world, especially for recreational purposes. A similar trend has been recently observed in Poland. A majority of Polish tourists visit European countries, most frequently those in the Mediterranean region, but each year an increasing number of travelers opt for more exotic holiday destinations in Asia, Africa and Central America. With tropical destinations becoming increasingly popular among Polish holidaymakers, family doctors have seen a rising number of patients who seek medical advice on the health risks prevalent in hot countries and health prevention measures to be taken in the tropics. A systematic increase in the number of visits to travel medicine websites provides evidence of the growing interest in this subject. On the increasingly popular www.medycynatropikalna.pl website, we have observed a growing number of searches for information concerning health risks in South-East and South Asia (Thailand, India, Vietnam, Sri Lanka), East Africa (Tanzania/Zanzibar, Kenya), the Caribbean (Dominican Republic), as well as information on vector-borne diseases (yellow fever, malaria), food- and waterborne diseases (typhoid, poliomyelitis), zoonoses (rabies) and sexually transmitted diseases (HIV/AIDS). The article presents the basic breadth of knowledge on travel medicine that a primary care practitioner must possess in order to be able to provide pre-travel, as well as post-travel, consultation to their patients.